The microfluidic system for studies of carcinoma and normal cells interactions after photodynamic therapy (PDT) procedures - Jedrych, Elzbieta (American Institute of Physics, 2011)

(untitled)
This study reports on the use of a microsystem for evaluation of photodynamic therapy (PDT) procedures on the “mixed” (carcinoma-normal) cultures. Balb/3T3 (normal mouse embryo) and A549 (human lung carcinoma) cells were tested in separated and “mixed” cultures. Interactions and migration of cells cultured together were observed. The PDT procedures were examined in the hybrid (PDMS/glass) microsystem which contains cell culture microchambers integrated with network of microchannels. We investigated that the number of dead cells after PDT procedures is dependent on the kind of cell culture. Moreover, the influence of the carcinoma cells on the viability of normal cells in the “mixed” culture was observed.